THE RELATIONSHIP BETWEEN WORKING ROOM TEMPERATURE AND SICK BUILDING SYNDROME IN HOSPITAL ADMINISTRATION OFFICERS - Devi Pramita Sari; Nabilatul Fanny; Intan Maharani (Proceeding of International Conference on Science, Health, And Technology, 2022)
The temperature of the workspace can affect the health condition of hospital administrative officers. One of the negative health impacts due to the less than ideal workspace temperature is Sick Building Syndrome. Based on the preliminary survey, it is known that there is 1 hospital administration officer who suffers from Sick Building Syndrome (SBS). The purpose of this study was to determine the relationship between workspace temperature and Sick Building Syndrome (SBS). The study used a descriptive survey and quantitative methods as well as a cross sectional study approach. The population and research samples were taken by total sampling, namely all hospital administration officers at the hospital as many as 7 respondents. The research instrument used a questionnaire. Quantitative data analysis used the chi-square relationship test. The results of this study from 7 respondents based on the results of the Chi-Square test, the significance of p between the independent variables, namely competence with the performance dependent variable, the results obtained were 0.03 (p <0.05), then Ho was rejected and it was stated that there was a relationship. The conclusion is that there is a relationship between workspace temperature and Sick Building Syndrome Hospital Administration Officers. Suggestions should provide knowledge of the importance of the ideal workspace temperature for the prevention of Sick Building Syndrome